Cafeteria Waste Valorization via Black Soldier Fly Larvae: A Sustainable Approach to Alternative Feed Development - Riana Septiani; Muhammad Nashiruddin; Susanti Sundari (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The increasing population and intensity of food service activities have contributed to a substantial rise in cafeteria waste volume. This organic waste, characterized by its complex nutrient and moisture content, poses serious environmental challenges, particularly through greenhouse gas emissions resulting from conventional landfill practices. Within the framework of the circular economy, this study explores the potential of bioconversion of cafeteria organic waste using Black Soldier Fly (BSF) larvae as an innovative and sustainable waste management solution. A quantitative experimental method was employed to evaluate the efficiency of waste mass reduction and to analyze the added value of the resulting BSF larvae as an alternative feed ingredient. The findings demonstrate a high effectiveness of BSF larvae in reducing waste volume, as indicated by an optimal Waste Reduction Index (13.98%), an efficient bioconversion rate (96.34%), and a favorable Feed Conversion Ratio (1.04). The process proved to be rapid and cost-efficient, with an operational cost of approximately IDR 3.5 million per month, generating both economic and environmental value.